Clinical communication skills - Washer, Peter (Oxford core texts series, 2009)
'Clinical Communication Skills' is a ground-breaking resource for medical students. It provides a practical introduction to the subject, with acknowledgement of key theories. Pragmatic worked examples will be of immediate benefit in clinical environments.